THE INFLUENCE OF INSTAGRAM ARTIST AS ENDORSER ON THE INTEREST IN PURCHASING MAYBELLINE PRODUCTS (Study on @sarahayuh_ Instagram Account Followers) - Thalitha Vania Agregati; Puji Lestari; Kurnia Arofah (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2017)
followers on Instagram (brand endorser). @sarahayuh_ was one of the Maybelline product endorsers who were considered to be aligning themselves with the image of the product to increase consumer purchasing power. The purpose of this study was to determine the effect of interest rate as the endorser of the appeal of the level of interest in purchasing Maybelline products on the @sarahayuh_’s Instagram account followers. This research method was a survey research. The population in this study was all the followers of @ sarahayuh_’s Instagram account with the sample numbers of 100 followers. The data analysis techniques used were product moment correlation analysis and simple linear regression analysis. The hypothesis in this research that there was positive influence and significant level of appeal as program endorser to the level of Maybelline products buying interest (Studies on @sarahayuh_’s Instagram Account Followers). The result of product moment correlation analysis obtained correlation coefficient value of 0.752, which means a positive and attraction significant of Instagram artist (instagram @ sarahayuh_) as endorser with interest in purchasing Maybelline products. Based on the regression analysis, it was found that interest in purchasing Maybelline products can be explained by the attraction of Instagram artist (Instagram @sarahayuh_) as an endorser, of 56.6%.